2021
DOI: 10.15587/1729-4061.2021.225418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patterns of crystal-chemical transformations in historical artifacts made of metals

Abstract: The theoretical substantiation of the process of elimination of individual chemical elements from crystal lattices of metals in the process of the crystal-chemical transformations taking place during the long history of artifact existence was given. To confirm the theoretical conclusions, five ancient gold items from different historical periods (from the IV century B.C. to the XVIII century A.D.) with approximately the same contents of gold, silver, copper, and iron in the alloy body were studied. The conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The experimental study, the results of which were reported earlier [1,3], makes it possible to draw the following conclusion. History artifacts that have survived under the conditions of burial and are known as archaeological finds have an extremely high rate of variability in the content of chemical elements in the results of measurement on different surface areas.…”
Section: Results Of Studying the Chemical Composition Of The Ash Obta...supporting
confidence: 53%
See 3 more Smart Citations
“…The experimental study, the results of which were reported earlier [1,3], makes it possible to draw the following conclusion. History artifacts that have survived under the conditions of burial and are known as archaeological finds have an extremely high rate of variability in the content of chemical elements in the results of measurement on different surface areas.…”
Section: Results Of Studying the Chemical Composition Of The Ash Obta...supporting
confidence: 53%
“…ent [2,3]. However, in that case, they proceed very slowlyfor hundreds, and sometimes thousands of years.…”
Section: This Paper Reports the Results Of Studying The Chemical Comp...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the surface of metal objects that have been made over the past 50 years, such high differences in chemical composition will not be observed, so this feature may be the main criterion for the authenticity of antique and museum samples of cold steel [4].…”
Section: The Aim Of the Work Is To Demonstrate The Practical Application Of Amentioning
confidence: 99%